Polycyclic aromatic compounds (PACs) in the Canadian environment: A review of sampling techniques, strategies and instrumentation. (November 2020) - Ahad, Jason M.E.; Macdonald, Robie W.; Parrott, Joanne L.; Yang, Zeyu; Zhang, Yifeng; Siddique, Tariq; Kuznetsova, Alsu; Rauert, Cassandra; Galarneau, Elisabeth; Studabaker, William B.; Evans, Marlene; McMaster, Mark E.; et al.
Abstract: A wide variety of sampling techniques and strategies are needed to analyze polycyclic aromatic compounds (PACs) and interpret their distributions in various environmental media (i.e., air, water, snow, soils, sediments, peat and biological material). In this review, we provide a summary of commonly employed sampling methods and strategies, as well as a discussion of routine and innovative approaches used to quantify and characterize PACs in frequently targeted environmental samples, with specific examples and applications in Canadian investigations. The pros and cons of different analytical techniques, including gas chromatography – flame ionization detection (GC-FID), GC low-resolution mass spectrometry (GC-LRMS), high performance liquid chromatography (HPLC) with ultraviolet, fluorescence or MS detection, GC high-resolution MS (GC-HRMS) and compound-specific stable (δ 13 C, δ 2 H) and radiocarbon (Δ 14 C) isotope analysis are considered. Using as an example research carried out in Canada's Athabasca oil sands region (AOSR), where alkylated polycyclic aromatic hydrocarbons and sulfur-containing dibenzothiophenes are frequently targeted, the need to move beyond the standard list of sixteen EPA priority PAHs and for adoption of an AOSR bitumen PAC reference standard are highlighted. Graphical abstract: Image 1 Highlights: Review of methods to collect samples for PAC analysis in the Canadian environment. Review of techniques used to quantify or characterize PACs in environmental samples. High-resolution MS and compound-specific isotope analysis offer unparalleled insight. The list of 16 EPA PAHs is insufficient for studies in Canada's oil sands region. The adoption of an Athabasca oil sands bitumen PAC reference standard is proposed. Abstract : A comprehensive review of sampling methods, strategies and analytical techniques used to quantify and characterize PACs in the Canadian environment.